Perspektif Siswa terhadap Penggunaan Google Classroom dalam Pembelajaran Bahasa Inggris - Rahma, Siti Rahmayana; Wanda, Eka; Auliya, Nur Izzatul; Jannah, Raodatul (PT. Riset Press International, 2025)
Along with the rapid advancement of digital technology, the use of media in learning has also undergone a significant transformation. Learning media is no longer just a visual or printed aid, but has developed into an interactive medium that bridges communication between educators and students. Advances in information and communication technology (ICT) also have a positive impact on language learning. Language, which is often referred to as the window to the world, is an important means of understanding and accessing global knowledge. Through the use of ICT, the language learning process becomes more interesting, interactive, effective, and efficient. The technology that is often used is Google Classroom. This study aims to explore students' views on the use of Google Classroom in learning English and identify the benefits and challenges faced by students when using Google Classroom in class XI SMAN 21 Makassar. This study uses a Quantitative method to explore students' views on the use of Google Classroom in English learning and identify the benefits and challenges faced by students when using Google Classroom in class XI SMAN 21 Makassar in 2025. The analysis in this study with Data Reduction, Categorization, Data Interpretation with a sample size of 46 respondents in class XI SMAN 21 Makassar. The data collection technique in this study used quaster random sampling in all classes XI SMAN 21 Makassar with a minimum of 6-10 respondents from various classes with data collection using a survey. The results of the study showed that there were 42 (0.92%) students with a positive view of the use of Google Classroom in Class XI SMAN 21 Makassar in 2025 and there were 4 (0.08%) students with a positive view of the use of Google Classroom in Class XI SMAN 21 Makassar in 2025, the benefits of using Google Classroom in the learning process, the majority answered More flexible access to materials and ease of collecting writing assignments were each chosen by 16 respondents (34%) in class XI SMAN 21 Makassar in 2025, the obstacles experienced by 46 respondents in using Google Classroom as a learning medium, the data above As many as 21 respondents (46%) stated that they did not experience any interference, which shows that most students feel comfortable and do not face significant obstacles in learning using Google Classroom in class XI SMAN 21 Makassar in 2025, As many as 19 respondents (41%) want more variety of materials in class XI SMAN 21 Makassar in 2025. 2025.